PENGONTROLAN RUANGAN DAN PENGAWASAN ASAP ROKOK MENGGUNAKAN PENDETEKSI ASAP MQ2 DAN CAMERA - Ernes, Risa Nadia; Defnizal, Defnizal; Wirawan, Nanda Tommy (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This research is in the form of emergency lights and security equipment in the room using Arduino which is made to assist the community in making it easier to activate/deactivate and avoid any danger as soon as possible in a special room. This system is made by designing, manufacturing and implementing a system of components that include a microcontroller as a controller and an LCD as an output to display system status and ADC values from sensors, AC and LED as room lighting, DVR Camera as output to record room conditions, and as an output. The MP3 module is the output of the sound information media which provides information on the status of the emergency and security lighting systems and information on the existence of a fire that is issued with the speaker as output according to the specified program. The system also uses an LDR Sensor to detect light in the room as input, an MQ2 Sensor as an input to detect smoke content, ACS712 Current Sensor as an input for measuring current from activating AC lights, and Remote Control as an input to manually activate and deactivate the system. The results of the study indicate that the tool made can work well and can be developed on a larger scale.